The Study of Subjective Pressure Sensation Developed by Foundation Garment (Journal of Fiber Bioengineering and Informatics, 2018)
The subjective wearing pressure sensation developed by foundation garment was surveyed and reported in this paper. Wearing experimental procedure was designed and fifteen female undergraduates were employed as subjects for this study. We obtained results of subjective wearing pressure sensation and shaping effect assessment through the questionnaire. Firstly, we studied the correlation between pressure evaluation, shaping effect assessment and time. Secondly, we analyzed the overall pressure sensation and different body part pressure sensation developed by corsets, three main factors were extracted from the 15 positions through statistical analysis, the subjective regression formula Y = -0.807 +0.499 X1 + 0.187 X3 was gained. The overall subjective pressure sensation had significant correlation with the waist (X1) and near waist (X3) pressure evaluation.